Phosphorus Analysis in Meat using UV-Vis Spectrophotometry with SnCl2 and Hydrazine Sulfate Reduction - Yussi Pratiwi; Rizky Amelia; Aulia Natasya (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2023)
This study aimed to optimize phosphorus analysis in meat using a molybdenum blue reaction involving SnCl2 and hydrazine sulfate as reducing agents to establish the most effective conditions for phosphorus detection. Meat, an essential source of nutrients like phosphorus, plays a vital role in human health, particularly bone and tooth strength. However, overconsumption of phosphorus can lead to health issues such as hyperphosphatemia, making regular monitoring of phosphorus levels in food necessary. The experiment used SnCl2 and hydrazine sulfate under varying acidic conditions to produce a stable blue complex indicative of phosphorus presence. The complex exhibited maximum absorbance in the 689–729 nm wavelength range. Validation of the method showed high linearity with R2 values of 0.9983 and 0.9984 for SnCl2 and hydrazine sulfate, respectively. The molar absorptivity for SnCl2 was 2.093 x 105 L mol-1 cm-1 and 7.92 x 104 L mol-1 cm-1 for hydrazine sulfate. Detection and quantification limits were established, and the %RSD values in each sample ranged from 1.08% to 1.93%, conforming to standard requirements. Upon analysis of meat samples, including duck, chicken, and beef, the phosphorus levels did not meet the Indonesian Nutritionist Association (PERSAGI) standards. This result emphasizes the need for regular phosphorus analysis in meat products to prevent health risks associated with excessive phosphorus intake, such as hyperphosphatemia.